2015
DOI: 10.1063/1.4922430
|View full text |Cite
|
Sign up to set email alerts
|

Plasma bullets behavior in a tube covered by a conductor

Abstract: In this work, for better applications of atmospheric pressure plasma jets, the physics of plasma streamers in a glass tube with a part of it covered by a conductor is investigated. To better understand the propagation mechanism of plasma bullets in capillary tubes passing through a curved or narrow passage for some biomedical or material applications, the propagation of plasma streamers in a tube covered by a floating conductor is investigated. For a plasma streamer propagating in a tube covered by a conductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In general, when a plasma is generated in a dielectric tube, it is believed that the dielectric tube will affect the plasma because of the charge accumulation on the inner surface of the quartz tube [37][38][39][40][41]. To understand the effect of the quartz tube on the plasma characteristics, studies with tube radius varied from micrometer to centimeter have been reported [42][43][44][45]. Investigations on the dynamic behavior of the plasmas generated in the tubes showed that most of them propagate in straight line.…”
Section: Introductionmentioning
confidence: 99%
“…In general, when a plasma is generated in a dielectric tube, it is believed that the dielectric tube will affect the plasma because of the charge accumulation on the inner surface of the quartz tube [37][38][39][40][41]. To understand the effect of the quartz tube on the plasma characteristics, studies with tube radius varied from micrometer to centimeter have been reported [42][43][44][45]. Investigations on the dynamic behavior of the plasmas generated in the tubes showed that most of them propagate in straight line.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the ring electrode can be treated as a floating electrode. Previous studies suggest that the floating electrode in front can facilitate the propagation of the IW due to its relative low electric potential [30, 31]. The peak values of the discharge currents in Figs.…”
Section: Resultsmentioning
confidence: 82%
“…This indicates that the electrical potential of the floating ring electrode is higher than 2.86 kV. By using the equal effect method [31], the electrical potential of the floating ring electrode was calculated to be about 3.1 kV.…”
Section: Resultsmentioning
confidence: 99%